Commensurate and incommensurate spin-density waves in heavy electron systems - P. Schlottmann (AIP Advances, 2016)
The nesting of the Fermi surfaces of an electron and a hole pocket separated by a nesting vector Q and the interaction between electrons gives rise to itinerant antiferromagnetism. The order can gradually be suppressed by mismatching the nesting and a quantum critical point (QCP) is obtained as the Néel temperature tends to zero. The transfer of pairs of electrons between the pockets can lead to a superconducting dome above the QCP (if Q is commensurate with the lattice, i.e. equal to G/2). If the vector Q is not commensurate with the lattice there are eight possible phases: commensurate and incommensurate spin and charge density waves and four superconductivity phases, two of them with modulated order parameter of the FFLO type. The renormalization group equations are studied and numerically integrated. A re-entrant SDW phase (either commensurate or incommensurate) is obtained as a function of the mismatch of the Fermi surfaces and the magnitude of |Q − G/2|.